2021
DOI: 10.7554/elife.67663
|View full text |Cite
|
Sign up to set email alerts
|

Strong confinement of active microalgae leads to inversion of vortex flow and enhanced mixing

Abstract: Microorganisms swimming through viscous fluids imprint their propulsion mechanisms in the flow fields they generate. Extreme confinement of these swimmers between rigid boundaries often arises in natural and technological contexts, yet measurements of their mechanics in this regime are absent. Here, we show that strongly confining the microalga Chlamydomonas between two parallel plates not only inhibits its motility through contact friction with the walls but also leads, for purely mechanical reasons, to inver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Previously, a directional swimming organism such a Chlamydomonas accumulates the corner in the geometrical chamber, and the phenomenon has been described as a theoretical model ( Théry et al, 2021 ). Although the cell accumulates in the corner without changing the behavioral state ( Mondal et al, 2021 ), we revealed that S. coeruleus , which is frequently found in a free-swimming form ( Reynierse and Walsh, 1967 ), tended to adhere to the chamber with the structure, and the behavioral change promoted accumulation in the crescent areas. The anterior end of the cell faces the opposite side of the dead end.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previously, a directional swimming organism such a Chlamydomonas accumulates the corner in the geometrical chamber, and the phenomenon has been described as a theoretical model ( Théry et al, 2021 ). Although the cell accumulates in the corner without changing the behavioral state ( Mondal et al, 2021 ), we revealed that S. coeruleus , which is frequently found in a free-swimming form ( Reynierse and Walsh, 1967 ), tended to adhere to the chamber with the structure, and the behavioral change promoted accumulation in the crescent areas. The anterior end of the cell faces the opposite side of the dead end.…”
Section: Discussionmentioning
confidence: 88%
“…On the other hand, when we modeled that the organisms probabilistically capture prey, the vortex array contributes to the positive efficiency of their feedings because the recirculation allows an increase in feeding chances of starfish larvae ( Gilpin et al, 2017 ). Additionally, vortex flow enhances the mixing and transport of substances, i.e., nutrients and wastes, around the cell ( Mondal et al, 2021 ). Combining our results and these reports, we determined that S. coeruleus adheres to narrow areas not only by avoiding being the prey of potential predators but also by capturing prey and mixing nutrients around the cell.…”
Section: Discussionmentioning
confidence: 99%
“…To characterise the flow in the aqueous phase, we consider a cylindrical squirmer of radius at low Reynolds number confined between two parallel plates separated by height . Because confinement strongly affects the flows generated by microswimmers (Mathijssen et al 2016; Jeanneret, Pushkin & Polin 2019; Mondal et al 2021), we follow the framework used in Jin et al (2021) to evaluate the flow field in the mid-plane between the plates. Specifically, we approximate the 3-D Stokes equations by the 2-D Brinkman equations (Brinkman 1947; Tsay & Weinbaum 1991; Pepper et al 2010; Gallaire et al 2014): Here, the permeability is defined as , in direct analogy with Darcy's law (Whitaker 1986), and is the slip length.…”
Section: Methodsmentioning
confidence: 99%
“…Chlamydomonas has a spheroidal shape with diameter of ∼ 10 µ m (Fig. 1a), swimming in (left-handed) helical trajectories at speed of ∼ 70 − 100 µ m/s while rolling around their long axis anticlockwise (observed from back) at 1-2 Hz [32]. Chlamydomonas has a red ‘eyespot’ that senses and converts light signals into coordination of ∼ 50-60 Hz beating patterns of its cis- and trans-flagellum, which enables the cell to steer its helical path in response to light and exhibit pho-totaxis.…”
Section: Oscillatory Phototaxis and Adaptation-induced Density Wavementioning
confidence: 99%